2013
DOI: 10.1242/jcs.126052
|View full text |Cite
|
Sign up to set email alerts
|

Apicobasal secretion of Wnt11 and Wnt3a in polarized epithelial cells is regulated by distinct mechanisms

Abstract: SummaryWnts are glycan-and lipid-modified morphogens that are important for cellular responses, but how Wnts are secreted in polarized epithelial cells remains unclear. Although Wntless (Wls) has been shown to interact with Wnts and support their secretion, the role of Wls in the sorting of Wnts to the final destination in polarized epithelial cells have not been clarified. Glycosylation was shown to be important for the sorting of some transmembrane and secreted proteins, but glycan profiles and their roles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 60 publications
3
71
0
Order By: Relevance
“…Wls is essential for the secretion of Wnts, and is trafficked to the basolateral membranes by AP-1 and clathrin from the trans-Golgi network (Port and Basler, 2010;Yamamoto et al, 2013). Consistent with these observations, knockdown of Wls completely suppressed Wnt5a secretion in polarized MDCK II/ Wnt5a cells, although the polarized distribution of podocalyxin and TfR was not impaired ( Fig.…”
Section: Polarized Secretion Of Wnt5asupporting
confidence: 80%
See 4 more Smart Citations
“…Wls is essential for the secretion of Wnts, and is trafficked to the basolateral membranes by AP-1 and clathrin from the trans-Golgi network (Port and Basler, 2010;Yamamoto et al, 2013). Consistent with these observations, knockdown of Wls completely suppressed Wnt5a secretion in polarized MDCK II/ Wnt5a cells, although the polarized distribution of podocalyxin and TfR was not impaired ( Fig.…”
Section: Polarized Secretion Of Wnt5asupporting
confidence: 80%
“…Our previous study also revealed that the majority of Wnt3a and Wnt11 are secreted basolaterally and apically, respectively, in polarized Madin-Darby canine kidney (MDCK) epithelial cells (Yamamoto et al, 2013). The basolateral traffic of Wnt3a requires adaptor protein 1 (AP-1) and clathrin, which are known to be important for the sorting of basolateral membrane proteins (Boehm and Bonifacino, 2001;Deborde et al, 2008;Fölsch, 2005).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations